Evolution of the Lebanese banking sector legitimacy in view of the pressure of the United States Regulations - NASSAR, Dany (Proche-Orient Études en management, 2020)
In the recent years, many international banks have been fined because of violations of US regulations. Also, their legitimacy was challenged, and questions were raised about the strategic responses adopted by these banks to restore their legitimacy. In Lebanon, the collapse of the Lebanese Canadian Bank (LCB) due to non-compliance with US regulations has shaken the whole banking industry whose legitimacy has been affected, in addition to the compliance measures taken by this sector in face of the mounting pressure of the US Legitimacy, a major concept of the neo institutional theory is crucial for the survival of organizations. This article postulates that the Lebanese banking sector is on continuous quest for the legitimacy of the US regulator on which it is dependent to survive. Thus, the aim of this paper is to explore how the Lebanese banking sector’s legitimacy has evolved over time in view of the pressure of the US, by addressing the following question: How the US regulations affect the perception of the Lebanese banking sector legitimacy? Towards achieving this objective, this paper utilizes a retrospective longitudinal design and undertakes a qualitative content analysis of archival data from 1997 to 2018. Our findings revealed that legitimacy in the Lebanese context has passed from a cognitive legitimacy conferred by a domestic regulator before LCB to a more “pragmatic” one that is conferred by a foreign regulator after LCB.